50.3k views
2 votes
Find all solutions to the system

Find all solutions to the system-example-1

1 Answer

6 votes

Answer:


x=-3\\y=5\\\\(-3,5)

Explanation:

Make both equations equal, as following:


y=y\\x^(2)+12x+32=6x+23

Add like terms:


x^(2)+12x+32-6x-23=0\\x^(2)+6x+9=0

Factor it as following:


(x+3)^(2)=0

Then:


x=-3 (Double root)

Substitute this into the second equation to obtain y:


y=6(-3)+23\\y=5

Then the solution is:


x=-3\\y=5\\\\(-3,5)

User Dallas Clark
by
5.9k points